Economic Perfomance and Work Activity in Sweden after the Crisis of the Early 1990s - Steven J. Davis; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2007)
Following a severe contraction in the early 1990s, the Swedish economy accumulated a strong record of output growth coupled with a disappointing performance in the labor market. As of 2005, hours worked per person 2064 years of age are 10.5 percent below the 1990 peak and a mere one percent above the 1993 trough. Employment rates tell a similar story. Our explanation for Swedens weak performance with respect to market work activity highlights the role of high tax rates on labor income and consumption expenditures, wage-setting arrangements that compress relative wages, business tax policies that disfavor labor-intensive industries and technologies, and a variety of policies and institutional arrangements that disadvantage younger and smaller businesses. This last category includes tax policies that penalize wealth accumulation in the form of owner-operated businesses, a pension system that steers equity capital and loanable funds to large incumbent corporations, and legally mandated job-security provisions that weigh more heavily on smaller and younger businesses. We describe these features of the Swedish institutional setup and provide evidence of their consequences based largely on international comparisons.
Keywords: D13; H30; J20; L52; O52; 330; Business taxation; Industry structure; Swedish economic performance; Tax effects; Time allocation; Wage-setting institutions; Work activity; Wirtschaftskrise; Wirtschaftsreform; Wirtschaftswachstum; Erwerbstätigkeit; Steuerbelastung; Schweden; USA